The Dimensional Obsessive-Compulsive Scale: Development and Validation of a Short Form (DOCS-SF) - Eilertsen, Thomas; Hansen, Bjarne; Kvale, Gerd; Abramowitz, Jonathan S.; Holm, Silje E. H.; Solem, Stian (Frontiers in Psychology, 2017)
Accurately and reliably measuring the presence and severity of Obsessive-Compulsive Disorder (OCD) symptoms is essential for both routine clinical work and research. The current study investigated psychometric properties of the dimensional obsessive-compulsive scale-short form (DOCS-SF). DOCS-SF was developed and validated in Norwegian. DOCS-SF contains a checklist with four symptom categories and five severity items scored on a zero to eight scale yielding a total score of 0-40. Data were collected from adults with a current diagnosis of OCD (n = 204) and a community comparison group (n = 211). The results provided evidence of internal consistency and convergent validity, although evidence for discriminant validity was mixed. Evidence was also found for diagnostic sensitivity and specificity, and treatment sensitivity. The analyses suggested a cut-off score of 16. In summary, the data obtained proved similar to studies published on the original dimensional obsessive-compulsive scale. There is strong evidence for the reliability and validity of the DOCS-SF for assessing OCD symptoms in individuals with this condition and in non-clinical individuals.